2001
DOI: 10.1007/pl00000272
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of thromboxane A2 and peptide leukotrienes in early and late phase nasal blockage in a guinea pig model of allergic rhinitis

Abstract: These results suggest that TXA2 and p-LTs, but not histamine, play important roles in both the early and the late phase nasal blockage in this model of allergic rhinitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
30
0

Year Published

2001
2001
2011
2011

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 41 publications
(42 citation statements)
references
References 29 publications
12
30
0
Order By: Relevance
“…A CysLT1-receptor antagonist, pranlukast, is now clinically used for treatment of allergic rhinitis in Japan. On the other hand, an involvement of CysLTs in the nasal obstruction has also been suggested in a guinea pig model of allergic rhinitis Yamasaki et al, 2001). Antigen inhalation to sensitized guinea pigs caused an increase in CysLTs in nasal cavity lavage fluids (Yamasaki et al, 2001).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A CysLT1-receptor antagonist, pranlukast, is now clinically used for treatment of allergic rhinitis in Japan. On the other hand, an involvement of CysLTs in the nasal obstruction has also been suggested in a guinea pig model of allergic rhinitis Yamasaki et al, 2001). Antigen inhalation to sensitized guinea pigs caused an increase in CysLTs in nasal cavity lavage fluids (Yamasaki et al, 2001).…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, an involvement of CysLTs in the nasal obstruction has also been suggested in a guinea pig model of allergic rhinitis Yamasaki et al, 2001). Antigen inhalation to sensitized guinea pigs caused an increase in CysLTs in nasal cavity lavage fluids (Yamasaki et al, 2001). The increase in upper airway resistance, an index of nasal obstruction, induced by antigen challenge in sensitized guinea pigs was inhibited by treatment with pranlukast Yamasaki et al, 2001).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a previous study, we found that sneezing induced within 1 h after challenge was almost completely suppressed by treatment with anti-histaminic drugs (19). This indicates that histamine released from mast cells immediately after pollen inhalation challenge plays a major role in the occurrence of sneezing.…”
Section: Discussionmentioning
confidence: 80%
“…From our previous findings regarding induction mechanisms of the nasal blockage, we can speculate two mechanisms: 1) Because we have demonstrated that cyteinyl leukotrienes (CysLTs) and thronboxane A 2 (TXA 2 ) are largely involved in the late phase nasal blockage (19,20), the aggravation of antigen-induced nasal blockage by the long-term treatment with BaP or 1-NP might be due to up-regulation of CysLT 1 and / or TP receptors and / or increases in the production of CysLTs and/ or TXA 2 . 2) Since the nasal blockage in our model is partly but significantly mediated by reactive oxygen species (ROS) (Mizutani et al, unpublished data) and antigen-induced production of ROS can be increased by treatments with DEP in sensitized rats (21), BaP and 1-NP also might up-regulate production of Each data value represents the mean ± S.E.M.…”
Section: Discussionmentioning
confidence: 99%